EXPERIMENTAL PROCESS FOR DETERMINING READING COMPREHENSION SKILLS - Sharapova Feruza Valiyevna (Scholar Express Journal, 2023)
This article is devoted to identifying and developing reading comprehension skills for students whose first language is Uzbek. The research is conducted among 9 th-grade students of Secondary Education, their first results in the process of working with the text were analyzed in this work. In the results, it can be seen that the students made a mistake in the task of concluding the general meaning of the text and its parts. These mistakes showed that a few of their language skills need improvement through development based on cognitive methods
Keywords: text; reading comprehension; the coherence of form and content; speech unity; practical skills; contextual meaning